A Forest of Pipes: Presenting the 37-pipe Sheng from the Inside - Baskind, Alexis; Wei, Wu (Circuit, 2022)
In the vast majority of existing studio and live productions, the sheng is represented as an external sound object, i.e., a sound source (typically positioned frontally) with a given distance and width, placed in a real or virtual space, as is commonly done for other featured instruments in music production. The empirical research presented here reverses the listening perspective. It develops methods for setting the listener metaphorically inside the sheng, surrounded by the pipes. It is similar to the image of the “forest of pipes” sometimes used for a church organ. This idea, which (though complex) may be technically easier to apply to the church organ, poses significant difficulties for the sheng because of its size and the radiation properties of the pipes (mostly directed outwards). Alternative methods for the design of the microphone system must therefore be sought.